2014
DOI: 10.1111/codi.12758
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and sexual dysfunction in women after resection with and without preoperative radiotherapy for rectal cancer: a population‐based cross‐sectional study

Abstract: Urinary and sexual problems are common in women after treatment for rectal cancer. Preoperative radiotherapy interferes with several aspects of urinary and sexual functioning. Bowel dysfunction after LAR is associated with urinary dysfunction and a reduction in sexual desire, activity and satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 36 publications
6
109
1
Order By: Relevance
“…However, this is not supported by our study, probably because of few patients who received APR surgery. On the other hand, some papers on female urinary and sexual dysfunction after resection with and without preoperative radiotherapy showed similar results to ours [24,25]. In terms of urinary function, although we saw no intergroup differences in mean IPSS scores, the changes in IPSS scores between baseline and the various follow-up time points are significantly different.…”
Section: Discussionsupporting
confidence: 86%
“…However, this is not supported by our study, probably because of few patients who received APR surgery. On the other hand, some papers on female urinary and sexual dysfunction after resection with and without preoperative radiotherapy showed similar results to ours [24,25]. In terms of urinary function, although we saw no intergroup differences in mean IPSS scores, the changes in IPSS scores between baseline and the various follow-up time points are significantly different.…”
Section: Discussionsupporting
confidence: 86%
“…However, the risk of either urinary or sexual dysfunction does seem heightened following total mesorectal excision compared with partial mesorectal excision, as well as after preoperative radiotherapy. 14,30,31 A limitation of the current study was that not all patients treated with curative surgery for rectal cancer in the study period underwent postoperative MRI or had their bowel function assessed. Of these patients, a subset of elderly patients, patients with disseminated disease, and patients with major comorbidities were exempted from follow-up or were not assessed for LARS.…”
Section: Length Of Remnant Rectum No Lars Minor Lars Major Larsmentioning
confidence: 99%
“…Nevertheless, in the studies performed recently, severe late effects have been confirmed in patients undergoing pelvic radiation therapy. The gastrointestinal problem is among them (30,31).…”
Section: Discussionmentioning
confidence: 99%